2014
DOI: 10.1073/pnas.1320412111
|View full text |Cite
|
Sign up to set email alerts
|

Using ancient DNA to study the origins and dispersal of ancestral Polynesian chickens across the Pacific

Abstract: Significance Ancient DNA sequences from chickens provide an opportunity to study their human-mediated dispersal across the Pacific due to the significant genetic diversity and range of archaeological material available. We analyze ancient and modern material and reveal that previous studies have been impacted by contamination with modern chicken DNA and, that as a result, there is no evidence for Polynesian dispersal of chickens to pre-Columbian South America. We identify genetic markers of authentic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
85
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 47 publications
9
85
0
1
Order By: Relevance
“…None of the letters in response to Thomson et al (1) undermine our conclusions. However, several issues have been raised, which we address in this reply.…”
mentioning
confidence: 48%
“…None of the letters in response to Thomson et al (1) undermine our conclusions. However, several issues have been raised, which we address in this reply.…”
mentioning
confidence: 48%
“…Red Junglefowl still commonly exist in their native habitats (Brickle et al., 2008; Brisbin, 1995) and are clearly distinguishable from domestic chickens (Johnsgard, 1999). Although genetic contributions from multiple Junglefowl species may have played a role in the domestication process (Eriksson et al., 2008; Nishibori, Shimogiri, Hayashi, & Yasue, 2005), archeological and genetic evidence (Fumihito et al., 1994, 1996; Gongora et al., 2008; Storey et al., 2012; Thomson et al., 2014) indicate that Red Junglefowl from Southeast Asia was the primary progenitor of all domestic breeds of modern chickens. In a previous study, we identified substantial haplotype variation in the major histocompatibility complex (MHC) B‐locus of wild Red Junglefowl (Fulton et al., 2016; Nguyen‐Phuc, Fulton, & Berres, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding when chickens were transported out of domestication centres and the directions in which they drifted provides information about prehistoric human migration patterns, trade routes and cultural diffusion (Thomson et al, 2014). Possible interactions may be reconstructed by mapping the presence of chickens in archaeological assemblages (Storey et al, 2008) using historical evidence (Peters, 1913;Crawford, 1984) also thought the mtDNA application (Liu et al, 2006, Miao et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In other case, some domestic chickens might have become feral with their descendants living as wild fowl (Miao et al, 2013). The various investigative techniques described above, do not substitute each other, but rather come together as different tools that complement each other in their specific specialisations to unravel the riddle of the history of domestication.Understanding when chickens were transported out of domestication centres and the directions in which they drifted provides information about prehistoric human migration patterns, trade routes and cultural diffusion (Thomson et al, 2014). Possible interactions may be reconstructed by mapping the presence of chickens in archaeological assemblages (Storey et al, 2008) using historical evidence (Peters, 1913;Crawford, 1984) also thought the mtDNA application (Liu et al, 2006, Miao et al, 2013.…”
mentioning
confidence: 99%